Analysis Of BEM Unisri's Publik Opinion Regarding Political Advertising Billhots "Kepak Sayap Kebhinekaan" - Herawati, Dewi Maria; Azhari, Wulan Ayu; Supuasari, Rahmatika Putri (PRoMEDIA, 2024)
Puan Maharani's billboard advertisement with the theme " Kepak Sayap Kebhinnekaan" raises many pros and cons in society. Many people think positively, but quite a few people sneer at the ad. This research wants to see the public opinion of a group of BEM Activists from Slamet Riyadi University, Surakrta regarding the billboard " Kepak Sayap Kebhinnekaan" as a political advertisement belonging to Puan Maharani. The method used in this research is descriptive qualitative. The results of this research are the responses given from several informants as BEM Activists at Slamet Riyadi University, Surakarta, which were variously positive, negative, and even neutral. There are those who openly do not support Puan Maharani to lead, but have a positive response to the message conveyed on Puan Maharani's political advertising billboards. Everyone who sees the political advertising billboard "Kepak Sayap Kebhinnekaan" of course has their own responses and opinions. Keywords: Public Opinion, Politic, Communication